Spletno nadlegovanje v šolah z vidika spola - Brečko, Barbara Neža (Šolsko polje, 2019)
Cyber violence is a form of peer violence and is a big problem both in the world and in Slovenia. Within the project Odklikni! a study was conduct-ed in the spring of 2018 in Slovenian primary and secondary schools, including 5290 young people. The survey a high proportion of adolescents who have already experienced cyber violence. The survey shows that victims of cyberbullying are more likely to be girls, which is in line with existing international studies. The article defines cyberviolence and various forms of cyber violence and gives a brief overview of the results of existing research. In this article, we focus on the findings of the research project Odklikni!. We analyze the views of young people on cyber violence, what types of harassment girls and boys experience, as the forms of harassment differs regarding the gender. As the results show, also in the experience of cyber violence, there are big gender differences - girls are much more concerned about violence, stressed, scared, helpless and depressed, and boys are more likely to consider cyber violence as fun, they don't care if they experience cyber violence, or it has no consequences for them. It could be said that boys are normalising cyber violence, or are not aware, it is a form of violence. Normalization occurs in both victims and perpetrators.
Keywords: cyberviolence; education; gender; ICT; IKT; medvrstniško nasilje; mladi; peer violence; spletno nadlegovanje; spol; Šolsko polje; The School field; vzgoja in izobraževanje; youth